Women’s Representation in Islamic Mass-Based Political Parties in Indonesia - Juwita Hayyuning Prastiwi; Andy Ilman Hakim (UIN Sunan Gunung Djati, 2024)
The results of the 2019 elections placed four political parties with a muslim constituent base PKB, PKS, PAN, and PPP into the parliament. The objectives of this research is to describe the accessibility of women in the membership and leadership of political parties, as well as their efforts to increase women's representation in public offices by Islamic mass-based political parties. This research was conducted using a feminist research methodology, which uses a qualitative research methods such as document analysis, literature review, and interviews. The findings are analyzed using feminist institutional theory, indicating that gender interest accommodation in the four mass-based Islamic political parties is weakly institutionalized. This is due to the formal regulations at the state level being implemented very weakly within the internal structures of political parties. The weakness of these formal regulations cannot be detached from the influence of informal institutions, where decision-making considerations often revert to gender-biased views resistant to positive gender-based changes.